2020
DOI: 10.4102/hsag.v25i0.1479
|View full text |Cite
|
Sign up to set email alerts
|

Improving nurses’ knowledge of managing endotracheal tube cuff pressure in intensive care units: A quasi-experimental study

Abstract: Background Previous studies conducted on nurses’ knowledge regarding endotracheal tube cuff pressure revealed that there were differences in intensive care nurses’ knowledge, leading to varying practices. Aim This study aimed to evaluate how an educational intervention based on the existing evidence-based guidelines, using both passive and active implementation strategies, could improve the knowledge of nurses regarding managing endotracheal tube cuff pressures in Malaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…The results support findings of previous studies that assessed the effect of training interventions on similar competencies; management of endotracheal tube cuff pressure 19 , cardiac life support skills of nursing staff in critical areas of care 18,31 , the care of a patient who is intubated and undergoing mechanical ventilation 32 , knowledge and practices of electrocardiogram interpretation 31,33 . As an example, the study by Bojsen et al 33 It is worth mentioning that the study was conducted before the corona virus disease (COVID-19) pandemic which has increased the demand for competent critical care nurses worldwide 35 .…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The results support findings of previous studies that assessed the effect of training interventions on similar competencies; management of endotracheal tube cuff pressure 19 , cardiac life support skills of nursing staff in critical areas of care 18,31 , the care of a patient who is intubated and undergoing mechanical ventilation 32 , knowledge and practices of electrocardiogram interpretation 31,33 . As an example, the study by Bojsen et al 33 It is worth mentioning that the study was conducted before the corona virus disease (COVID-19) pandemic which has increased the demand for competent critical care nurses worldwide 35 .…”
Section: Discussionsupporting
confidence: 85%
“…The significant increase in the participants' overall competence and scores on three domains of competence; knowledge, skill and experience after the training is consistent with the outcome of similar training programmes in critical care settings in Malawi and other developing countries 16 , 19 , 28 – 30 . For example, the study by Pubudu 30 on nursing intensive care skills training in Sri Lanka, reported that post-test scores of participants were significantly higher than pre-test scores.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations